1982
DOI: 10.1128/aac.22.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in susceptibilities of Proteeae spp. to six cephalosporins and three aminoglycosides

Abstract: Six cephalosporins and three aminoglycosides were examined for activity against 1,693 isolates belonging to six species of Proteeae. The most notable species-specific differences included the marked susceptibility of Providencia alcalifaciens and Proteus mirabilis to cephalothin, the resistance of Proteus vulgaris to cefamandole, and the resistance of Providencia stuartii to gentamicin and tobramycin. The third-generation cephalosporins cefotaxime and moxalactam were substantially more inhibitory than were cef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…AGENTS CHEMOTHER. This has been confirmed for the aninoglycosides and cephalosporins by a recent study- (10) in which Providencia stuartii was found to be typically resistant to gentamicin and tobramycin, whereas Providencia alcalifaciens was susceptible. Providencia stuartii is known to commonly produce aminoglycoside 2'-Nacetyltransferase which is chromosomally mediated (8).…”
mentioning
confidence: 63%
“…AGENTS CHEMOTHER. This has been confirmed for the aninoglycosides and cephalosporins by a recent study- (10) in which Providencia stuartii was found to be typically resistant to gentamicin and tobramycin, whereas Providencia alcalifaciens was susceptible. Providencia stuartii is known to commonly produce aminoglycoside 2'-Nacetyltransferase which is chromosomally mediated (8).…”
mentioning
confidence: 63%
“…This new and simple method for routine identification of species of Proteeae is likely to assume clinical importance, because strains from this group are often responsible for hospital-acquired infections, and the possibility of rapidly identifying them would be of great help in tracing the origin and spread of nosocomial outbreaks. Furthermore, highlevel and multiple antibiotic resistance is very frequent among P. stuartii, while it is quite uncommon among the other species of Proteeae (5,10,11,18). Thus, accurate identification to species level of Proteeae isolates is essential to avoid potentially misleading indications; even today, however, most of the surveys of susceptibilities to antimicrobial agents fail to fully separate the species of the tribe Proteeae, often splitting them into Proteus mirabilis, indolenegative Proteus species, and Providencia spp.…”
Section: Discussionmentioning
confidence: 99%
“…A distinctive feature of P. stuartii strains is that unlike all the other species in the Proteeae group, they often present with multiple resistance to disinfectants and antibacterial agents (4, 9,10,17,19). However, susceptibility to expanded-spectrum cephalosporins is usually maintained.…”
mentioning
confidence: 99%